Provision of Resources for Communicative Competence Development of a Future Manager of Educational Institution as a Component of Pedagogic Management Culture - Гуменникова, Тамара Рудольфівна (Pedagogy of Higher and Secondary Education, 2013)
Gumennikova T. R. Provision of Resources for Communicative Competence Development of a Future Manager of Educational Institution as a Component of Pedagogic Management Culture The article presents the ways of communicative competence development of a future manager of educational institution. Foreign language proficiency is revealed to be important for a modern manager in educational area. The experimental research enabled to model and to test the learning environment resources of Ukrainian university that prepares managers of educational institutions. The present paper determines the stages of Master Training process relating to the foreign language proficiency improvement in the frames of professional development.